2021
DOI: 10.1017/s0952675721000245
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Breton word stress: new speakers and the influence of French

Abstract: This paper investigates stress patterns in Breton across speakers of different ages and with different linguistic backgrounds. Centuries of contact with French have led to French influence in Breton lexis, phonology and morphosyntax, and Breton's current status as an endangered minority language makes it vulnerable to further change. Additionally, younger ‘new speakers’ of Breton, who have acquired the language through Breton-medium education, are said to transfer features from French into their Breton. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…As part of a larger study of metrical stress in Breton, fieldwork was undertaken in southwest Brittany, within the kerneveg dialect area (see Kennard 2021). Two groups of speakers were interviewed: older, traditional speakers aged 57-83 (mean age = 73.4) who had grown up speaking Breton at home with their families, and younger, 'new' speakers aged 27-52 (mean age = 38.3) who had acquired Breton largely through immersion or bilingual schooling, with no or little input from relatives at home.…”
Section: Pilot Studymentioning
confidence: 99%
See 3 more Smart Citations
“…As part of a larger study of metrical stress in Breton, fieldwork was undertaken in southwest Brittany, within the kerneveg dialect area (see Kennard 2021). Two groups of speakers were interviewed: older, traditional speakers aged 57-83 (mean age = 73.4) who had grown up speaking Breton at home with their families, and younger, 'new' speakers aged 27-52 (mean age = 38.3) who had acquired Breton largely through immersion or bilingual schooling, with no or little input from relatives at home.…”
Section: Pilot Studymentioning
confidence: 99%
“…Palosaari & Campbell (2011) note that morphophonological features of minority languages which are not found in the dominant language are susceptible to loss in the context of language shift. It has also been observed that younger Breton speakers may transfer French features into their Breton, and this includes the use of French‐influenced stress patterns (Madeg 2010; Kennard 2021).…”
Section: Pilot Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Dialectal substrates (Carton et al 1983) and broader language contact (e.g. Sichel-Bazin et al 2011;Kaminskaïa & Poiré 2012;Mamode 2015;Kennard 2021) are particularly common explanations. Martin (2004), however, proposes that prominence shift is due to archaic tendencies and therefore that it is conservative, rather than innovated or induced by contact.…”
Section: Introductionmentioning
confidence: 99%